Shifts in Public Interest in Private Islamic Educational Institutions: A Study of the Zoning System Policy - Lubis, Ardiansyah (LPPM Universitas Ibn Khaldun, Bogor, 2025)
The school zoning policy, as outlined in the regulations of the Ministry of Education and Culture of the Republic of Indonesia, aims to ensure equitable access to education. However, implementing this system presents significant challenges for educational institutions, especially when it comes to attracting new students. This study examines the shift in public interest in private Islamic educational institutions resulting from the policy. A systematic review of 278 articles was conducted, and 17 articles were selected based on predetermined inclusion and exclusion criteria. These criteria were meticulously defined and applied in accordance with the PRISMA guidelines, encompassing a wide range of sources from Scopus, Google Scholar, and Lens.org. Org. Existing research suggests that the public has limited ability to choose schools that align with their children's interests and talents. This impacts learning motivation and satisfaction with the education received. Consequently, private Islamic educational institutions have the opportunity to attract high-quality students by offering a curriculum that is more responsive to community needs